2021
DOI: 10.3390/molecules26133861
|View full text |Cite
|
Sign up to set email alerts
|

Biotransformation of Timosaponin BII into Seven Characteristic Metabolites by the Gut Microbiota

Abstract: Timosaponin BII is one of the most abundant Anemarrhena saponins and is in a phase II clinical trial for the treatment of dementia. However, the pharmacological activity of timosaponin BII does not match its low bioavailability. In this study, we aimed to determine the effects of gut microbiota on timosaponin BII metabolism. We found that intestinal flora had a strong metabolic effect on timosaponin BII by HPLC-MS/MS. At the same time, seven potential metabolites (M1-M7) produced by rat intestinal flora were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Although accumulative studies confirmed that berberine, the main alkaloid component of Phellodendri Chinensis Cortex, can protect cognitive function (Aski et al, 2018;Shinjyo et al, 2020;Yi et al, 2021), subsequent studies gradually recognized that regulating intestinal flora may be the initial link of berberine improving cognitive function (Zhang et al, 2020b;Habtemariam, 2020). The ZSWF components metabolized by intestinal flora of DCI mice may be saponins in Anemarrhenae Rhizoma (Tian et al, 2016;Dong et al, 2021). Furthermore, besides the immune signaling pathway investigated in this study, the mechanism of ZSWF regulating intestinal flora to improve DCI may also include the following aspects: first, regulating the tryptophan-kynurenine metabolic pathway.…”
Section: Discussionmentioning
confidence: 91%
“…Although accumulative studies confirmed that berberine, the main alkaloid component of Phellodendri Chinensis Cortex, can protect cognitive function (Aski et al, 2018;Shinjyo et al, 2020;Yi et al, 2021), subsequent studies gradually recognized that regulating intestinal flora may be the initial link of berberine improving cognitive function (Zhang et al, 2020b;Habtemariam, 2020). The ZSWF components metabolized by intestinal flora of DCI mice may be saponins in Anemarrhenae Rhizoma (Tian et al, 2016;Dong et al, 2021). Furthermore, besides the immune signaling pathway investigated in this study, the mechanism of ZSWF regulating intestinal flora to improve DCI may also include the following aspects: first, regulating the tryptophan-kynurenine metabolic pathway.…”
Section: Discussionmentioning
confidence: 91%
“…Compound 11, characterized by the molecular formula of C 45 H 76 O 19 , fragment ions at m/z 901.4813 [M‐H‐H 2 O] − , m/z 757.4384 [M‐H‐C 6 H 10 O 5 ] − , and m/z 595.3843 [M‐H‐C 6 H 10 O 5 ‐C 6 H 10 O 5 ] − , was identified as timosaponin B‐II according to the reference substance and reported data [30]. It could be detected in all bio‐samples of CHF rats (Figure 7).…”
Section: Resultsmentioning
confidence: 99%
“…According to research reports, these saponins have antidepressant and antineuritis pharmacological activities. Guo-Ming Dong et al found that the gut microbiota has a strong metabolic effect on timosaponin BII, which can be converted into 7 characteristic metabolites [ 36 ]. Considering that the phytochemical-microbiota interaction is the key to drug metabolism, we will focus our research on the influence of DMNS on the abundance, diversity and function of the gut microbiota of ADHD rats.…”
Section: Discussionmentioning
confidence: 99%